2006
DOI: 10.1126/science.1124070
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of RET Regulatory Function from Human to Zebrafish Without Sequence Similarity

Abstract: Evolutionary sequence conservation is an accepted criterion to identify noncoding regulatory sequences. We have used a transposon-based transgenic assay in zebrafish to evaluate noncoding sequences at the zebrafish ret locus, conserved among teleosts, and at the human RET locus, conserved among mammals. Most teleost sequences directed ret-specific reporter gene expression, with many displaying overlapping regulatory control. The majority of human RET noncoding sequences also directed ret-specific expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
297
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 342 publications
(324 citation statements)
references
References 27 publications
26
297
0
1
Order By: Relevance
“…Other works have indicated that mammalian enhancers can drive expression to zebrafish embryos in the absence of overt sequence conservation [39,43,74,75], but in these studies it was not clear whether the mammalian enhancers had originated de novo in the mammalian lineage or if they were divergent orthologues to those of zebrafish. As indicated by the work of Taher et al [45], which used NCEs of the amphibian Xenopus as an intermediate species to find divergent mammalian and zebrafish NCEs, orthologous vertebrate enhancers can become so dissimilar by extensive mutations in TFBSs and intervening sequences that computer algorithms may fail to identify them.…”
Section: Discussion (A) Conservation Of Function By Non-homologous Enmentioning
confidence: 99%
“…Other works have indicated that mammalian enhancers can drive expression to zebrafish embryos in the absence of overt sequence conservation [39,43,74,75], but in these studies it was not clear whether the mammalian enhancers had originated de novo in the mammalian lineage or if they were divergent orthologues to those of zebrafish. As indicated by the work of Taher et al [45], which used NCEs of the amphibian Xenopus as an intermediate species to find divergent mammalian and zebrafish NCEs, orthologous vertebrate enhancers can become so dissimilar by extensive mutations in TFBSs and intervening sequences that computer algorithms may fail to identify them.…”
Section: Discussion (A) Conservation Of Function By Non-homologous Enmentioning
confidence: 99%
“…Although many of the key enzymes responsible for deposition and maintenance of H3K27me3 are known, it is likely that we do not have a complete catalog of all the elements of all PREs (Delest et al 2012), nor do we know the exact spatial or orientation requirements of the involved binding sites (if indeed there are any). However, the extreme conservation of H3K27me3 across distantly related species leads to the question of how a cis-regulatory element composed of relatively degenerate sequence motifs could persist functionally over such a long period of time (Ruvinsky and Ruvkun 2003;Fisher et al 2006).…”
Section: H3k27me3 Conservation Bypassed By Gene Duplicationmentioning
confidence: 99%
“…All sequences were tested for enhancer activity in the Hb using our established zebrafish transgenesis pipeline (Fisher et al 2006;McGaughey et al 2008). We define hindbrain expression as any expression in the CNS region that is posterior to the midbrain …”
Section: Genome-wide Predictions Identify Novel Hindbrain Enhancersmentioning
confidence: 99%
“…Short fragment sequences for HB01 and HB16 were synthesized as double-stranded oligos, A overhangs added, then cloned as predicted enhancers. At least 100 embryos were injected per construct at the two-cell stage with tol2 transposase as previously described (Fisher et al 2006). Injected embryos were screened for GFP expression in the CNS at 24 and 48 hpf.…”
Section: Hindbrain Genesmentioning
confidence: 99%